Students’ Level of Knowledge of SDN Tatah Alayung on the Environmentally Conscious and Disaster Mitigation School Program in A Wetland Environment - Efendi, Muhammad; Muhtar, Ghinia Anastasia; Sugianto, Akhmad; Ramadani, Dwi; Rahmawati, Rahmawati (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Schools with Environmental Insight and Disaster Mitigation (SWALIBA) are part of educational institutions that are committed to and systematically integrating environmental values, and disaster preparedness attitudes into all aspects of school activities. The SWALIBA process involves three stages, namely development, progress, and service, which reflect the condition and readiness of the school to run this program. SDN Tatah Alayung is currently in the preparation stage to become a SWALIBA school, which requires physical and non-physical preparation. An assessment of the physical aspects of the school has been carried out to evaluate the readiness to implement SWALIBA at SDN Tatah Alayung, and the results will be presented in scientific articles and activity reports. The approach methods in the Community Partnership Program include counseling, discussion, training, simulation, mentoring, monitoring, and evaluation of activities. Program evaluation shows that the level of student understanding at SDN Tatah Alayung is 96.79%, categorized as good. However, in terms of mitigation, training, simulation, and outreach regarding disasters in swamp areas, improvement still needs to be done because students' understanding is still below 50%. The analysis results were obtained from 53 respondents from class IV, V, and VI students. The technology that was successfully implemented involved changing attitudes and habits through outreach activities, discussions, training and simulations, as well as creating an attractive SWALIBA pocketbook for elementary school students.